Human Rights in the Prospect of Implementing Non-Conviction Based Asset Forfeiture in Corruption Cases in Indonesia - Vincentius Patria Setyawan; Hartiwiningsih; Erna Dyah Kusumawati (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
Non-Conviction Based Asset Forfeiture (NCB AF) is an alternative legal mechanism that allows the state to recover assets derived from corruption without requiring a prior criminal conviction. This mechanism has gained global relevance as corruption often involves complex transactions, shell companies, and transnational financial flows that hinder criminal prosecution. However, the application of NCB AF raises significant human rights concerns, particularly regarding the presumption of innocence and the right to property. This study examines the human rights implications of implementing NCB AF in corruption cases within Indonesia’s legal system using a normative juridical and comparative approach. The comparative analysis draws insights from the United Kingdom, the United States, and the Philippines jurisdictions that have successfully balanced asset recovery objectives with fundamental rights protections. The findings indicate that while NCB AF strengthens Indonesia’s anti-corruption strategy, its implementation must incorporate strict procedural safeguards and judicial supervision to prevent arbitrary deprivation of property. The study concludes that a balanced legal framework integrating effective asset recovery with human rights protection is essential to ensure justice, accountability, and the legitimacy of the state’s anti-corruption efforts.